Playful-consumption experience in digital game playing: A scale development - Abbasi, A.Z. (Springer Verlag, 2017)
This paper intends to develop a scale to measure a videogame player’s emotional, sensory, and imaginal experiences in digital gaming. We first define the construct of playful-consumption experience in videogame playing and accordingly, develop a scale for measuring playful experiences in videogames. We collected the data of 225 valid respondents which were further analyzed through exploratory factor analysis (EFA) and reliability analysis. The results of EFA and reliability analysis reported that the loaded items were emerged into a seven factor solution and all constructs have good reliability. This study is unique in the videogame literature as it uses the theoretical definition of playful-consumption experience to define and measure the player’s experiences in videogame playing as playful-consumption experience of videogame play. © IFIP International Federation for Information Processing 2017 Published by Springer International Publishing AG 2017. All Rights Reserved.